Research on cultural diversity and sustainable land-use management assessment model - Wang, Ying; Zhang, Junqiao (Frontiers in Environmental Science, 2024)
This study quantitatively evaluated the role of cultural diversity and psychological awareness in sustainable land-use management (SLUM). Firstly, an assessment model based on fuzzy analytic hierarchy process is established by combining fuzzy logic, expert knowledge and analytic hier-archy process. The model addresses the uncertainty of qualitative assessment and adapts to dy-namic environments and complex human behavior. The research process included a literature review and expert consultation to identify key factors influencing land use and assign weights to these factors through FAHP. Subsequently, FAHP determined that cultural diversity had the highest weight among all considerations, indicating the urgent need to respect and integrate local cultural diversity in land management. Psychological awareness follows closely, suggesting that land-use decisions are profoundly influenced not only by tangible economic and environmental conditions, but also by the psychological states, knowledge levels, value systems, and social perceptions of groups and individuals. These findings highlight the need to consider and integrate these intangible factors when developing land management strategies. This approach fosters broad social acceptance and participation, ultimately moving towards the long-term goal of sustainable land use. Finally, the study provides decision-makers with a tool for identifying subtle differences at the cultural and psychological levels that can help develop more nuanced and personalized management options for different land use strategies.